Regional Workshop on Root Crops Production and Research in the Caribbean (1985, Guadeloupe). Root crops production and research in the Caribbean (International Center for Tropical Agriculture, 1985)
In July 1985 a regional workshop on cassava was held in Guadeloupe to identify and define common regional constraints to root crop development, evaluate the potential for further development of root crops in the region, and develop a program for regional network activities. Individual country reports presented discuss the role of the different root crops in the country`s agricultural economy, socioeconomic characteristics of root crop farmers, production and marketing, government policies, and research and training activities. (CIAT)